Advanced lighting current generators - Quyen, Huy Ánh; Nguyen, Mạnh Hùng; Ta, Văn Minh (Journal of Technical Education Science, 2010)
Researches in lightning current impulse circuit have used various schematics for diverse impulses, which makes several problems for lightning current impulse generator fabrication at a suitable cost. In addition, errors of several lightning current impulse math models have not met the standards. This article presents some solutions to the determination of parameters for a significant lightning current impulse circuit and a lightning current impulse math model which is in Matlab environment with high accuracy.